Decoration of Ti/TiO2 Nanotubes with Pt Nanoparticles for Enhanced UV-Vis Light Absorption in Photoelectrocatalytic Process - Almeida, Lucio C. [UNESP]; Zanoni, Maria V. B. [UNESP] (Soc Brasileira Quimica, 2014)
Pt nanoparticles were decorated on TiO2 nanotube arrays (TiO2NTs) by cathodic deposition. These nanoparticles were uniformly distributed, highly separated and spaced all over TiO2NT surface to shorten deposition times with Pt particle sizes proportional to the applied charges. The Pt/TiO2NT photoelectrode shows an intense absorption peak in the visible region with a significant red shift induced by Pt deposited on TiO2NT surface, decreasing the band gap energy from 3.21 eV to 2.87 eV. Pt/TiO2NT photoelectrode was tested as photoanode in the photoeletrocatalytic oxidation of Acid Red 29 dye with great success. Total decolorization and 92% of total organic carbon removal were obtained after 120 min of treatment by using Pt/TiO2NT photoelectrode which was superior to the values obtained for the undecorated one (87% and 68%, respectively) due to better use of irradiation and minimization of charge recombination.
Keywords: photoelectrocatalytic process; Pt decorated TiO2; dye degradation